2020
DOI: 10.1016/j.celrep.2020.108206
|View full text |Cite
|
Sign up to set email alerts
|

tagHi-C Reveals 3D Chromatin Architecture Dynamics during Mouse Hematopoiesis

Abstract: Highlights d Low-input tagHi-C captures the chromatin structures using hundreds of cells d Compartment and the Rabl configuration are dynamic during hematopoiesis d Gene-body-associating domains (GADs) are general structures of highly expressed genes d Spatial chromatin loops link GWAS SNPs to candidate bloodphenotype genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 65 publications
2
58
0
Order By: Relevance
“…Previous analysis by Lara-Astiaso et al [54] reported a set of critical genes for hematopoietic lineage differentiation; we identified 12 of the 13 at an FDR value < 0.01 ( Supplemental Figure S4 ). We also found supporting evidence for some examples of lineage-specific genes highlighted by Zhang et al, 2020 [28]. The authors showed that increased gene-body associating domains (GAD) scores are linked to active transcription and indicate cell-type specific features.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Previous analysis by Lara-Astiaso et al [54] reported a set of critical genes for hematopoietic lineage differentiation; we identified 12 of the 13 at an FDR value < 0.01 ( Supplemental Figure S4 ). We also found supporting evidence for some examples of lineage-specific genes highlighted by Zhang et al, 2020 [28]. The authors showed that increased gene-body associating domains (GAD) scores are linked to active transcription and indicate cell-type specific features.…”
Section: Resultssupporting
confidence: 86%
“…We observed very similar proportions for A and B compartments except for two cell types (granulocyte-macrophage progenitor (GMP) and megakaryocyte-erythrocyte progenitor (MEP)), where the primary cells showed a lower frequency of A compartments ( Figure 5A ). We detected a total of 2,569 differential compartments across the ten cell types encompassing many of the genomic regions previously shown to undergo dynamic changes [28]. Another observation was an overall higher proportion of A compartments in the differential regions other than MEPs.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A CoolBox figure representing differential interactions of Hi-C contact matrices. Shown Hi-C and RNA-Seq data are produced from the process of hematopoietic differentiation[25]. Its clearly that there is a topological association domain(TAD) formation at the Abca13 gene region and its RNA expression is up-regulated at the same time after the differentiation.…”
Section: Resultsmentioning
confidence: 99%